1956
DOI: 10.6028/jres.056.003
|View full text |Cite
|
Sign up to set email alerts
|

Pyrochlore-type compounds containing double oxides of trivalent and tetravalent ions

Abstract: A study has been mad e by X-ray diffract ion analyses of t he A20 3 :2B02-type double oxides. It was found that many of t hese mixed oxides, after appropriate heat treatment, formed compounds of the formula type A2B20 7• Most of these compounds crystallized in the cubic system with a face-centered cell similar to that found for the mineral pyrochlore, although some were distorted from the ideal cubic struct ure.Ind exed X-ray diffraction powder patterns are given for t he cubic compounds 811l203· 2Ti02, Gd 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
2

Year Published

1978
1978
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(62 citation statements)
references
References 7 publications
2
57
1
2
Order By: Relevance
“…Analysis of the room-temperature x-ray diffraction data collected on the powder used to prepare the feed rods showed that the calculated value of the lattice parameter (a = 10.682 87(5)Å) is, in this case, very similar to that reported in the literature [29,37].…”
Section: B Crystal Structuresupporting
confidence: 62%
See 1 more Smart Citation
“…Analysis of the room-temperature x-ray diffraction data collected on the powder used to prepare the feed rods showed that the calculated value of the lattice parameter (a = 10.682 87(5)Å) is, in this case, very similar to that reported in the literature [29,37].…”
Section: B Crystal Structuresupporting
confidence: 62%
“…Studies of the magnetic properties have shown that the Pr 3+ ions in Pr 2 Zr 2 O 7 have a ground-state doublet with a local Ising anisotropy along 111 axes and are coupled by an antiferromagnetic exchange, but no long-range magnetic order is observed down to very low temperatures (76 mK) [21,24,25]. The spin ice-like correlations revealed by elastic magnetic neutron scattering, the broad excitation spectrum observed in the low-energy inelastic neutron scattering, and the reduction of the nuclear contribution to the heat capacity [24] may be connected with the strongly anisotropic superexchange and multipolar interactions [26,27] • C, although the melting point was not established [29]. The order-to-disorder transition in Nd 2 O 3 -ZrO 2 occurs at 2300…”
Section: Introductionmentioning
confidence: 99%
“…Polycrystalline powdered samples of Dy 2 Ti 2 O 7 and (DyY)Ti 2 O 7 were prepared using well established solidstate synthesis techniques 29 . The Y 3+ ion was used for magnetic dilution since it has nearly the same ionic radius as Dy 3+ .…”
Section: Methodsmentioning
confidence: 99%
“…The diffraction refl exes for La 2 Zr 2 O 7 were no longer observed after reheating (see Supporting Information Figure S20), suggesting redissolution of the La 2 Zr 2 O 7 into the monoclinic phase. The La concentrations for the particles (3% and less) are borderline with the range for solid solubility in monoclinic zirconia, as given by the phase diagrams for the La 2 O 3 -ZrO 2 system, [22][23][24] but are higher than maximum solubility of 1% La reported by Bastide et al [ 21 ] Lastly, after heating at 1500 °C, all samples were fully sintered and had lost their spherical shape, as shown in the Supporting Information ( Figure S4). …”
Section: Stability Of La-doped Microparticlesmentioning
confidence: 99%
“…[21][22][23][24] La 2 Zr 2 O 7 and Gd 2 Zr 2 O 7 have been considered for TBC applications due to their high melting points, phase stabilities, and low thermal conductivities. However, their use is impeded by a low toughness compared to YSZ [ 25 ] and a thermal expansion mismatch between the coating and metallic layer in the components.…”
Section: Introductionmentioning
confidence: 99%